'Nobody will thank me for this': Championing the ERA - Schilo, Ann (Routledge: Taylor and Francis Group, 2012)
In recent years there has been a shift within Australian Universities to a corporate model of management rather than the collegial approach of the past. Concomitantly, Federal government funding mechanisms have required greater accountability for its financial investment in the sector's research activities. In turn, the daily life of an Australian scholar has undergone a significant transformation. In this current audit culture, academic staff are required to deal with the conflicting demands of onerous teaching commitments, emphasis on increased research production and the devolving of ever burgeoning administration to their own desktops. While University research communities were negotiating the requirements for the 2009–2010 Excellence in Research for Australia (ERA) assessment, academic life proved particularly challenging for scholars whose work spans both traditional and non-traditional forms of research publication. This paper considers the implications of ERA for staff working in non-traditional research areas and the various negotiations they had to make between the requirements established by ERA and university administration and their own research inclinations. In particular, it focuses on the activities of the ‘champions’, those assigned the task of collecting and collating the information, the challenges they faced and the strategies they employed to deal with often conflicting impulses; on one hand the need to comply with reporting requirements and on the other, the reticence of their colleagues as well as their own misgivings. In so doing this paper reflects upon the tensions encompassing contemporary scholarly affairs.